Identity and Anonymity in Lady Mount Cashell's 1798 Rebellion Broadside. (17th May 2022) - Wolf, Alexis
Abstract: This article attributes a republican broadside of the 1798 Irish Rebellion to Anglo‐Irish aristocrat Margaret Moore, Lady Mount Cashell. I consider 'The Bard of Erin' broadside in light of several overlapping factors including Mount Cashell's earlier relationship with her governess Mary Wollstonecraft, participation in women's networks of antiquarian sociability in Dublin and her affinity with the United Irish cause. The broadside exemplifies Enlightenment ideals of classical republicanism in Ireland, while Mount Cashell's anonymous involvement illustrates the often‐concealed contribution of women writers to radical print culture. The article includes the full text of 'The Bard of Erin'.